The Impact of Artificial Intelligence Technologies on Financial Sustainability in Banks A Field Study on a Sample of Sudanese Banks (Sebha University Conference Proceedings, 2025)
The study aimed to identify the impact of artificial intelligence (AI) technologies, specifically predictive analytics, machine learning, and big data processing, on financial sustainability. The descriptive-analytical method was employed, and the study population consisted of administrative leaders in Sudanese banks, totaling 188 individuals. A comprehensive survey was conducted by distributing an electronic questionnaire to the entire study population, of which 137 responded. The study reached several findings, including that Sudanese banks utilize AI technologies in their financial sustainability operations. The level of financial sustainability in the sampled banks was high, with a mean score of 4.12. Furthermore, the study found a statistically significant impact of AI technologies, in all their dimensions collectively, on financial sustainability in Sudanese banks. The study recommended the adoption of a comprehensive strategy for utilizing AI technologies across various banking operations in Sudan. This includes establishing an integrated infrastructure and training qualified human resources to achieve financial sustainability. Additionally, it emphasized the importance of enhancing financial resource management to enable Sudanese banks to adapt to potential crises and maintain financial stability. The study also highlighted the need to implement smart technologies in Sudanese banks to improve operational efficiency and meet customer needs, thereby supporting long-term financial sustainability and reducing costs..